Audit simulation and learning styles: Enhancing students' experiential learning and performance at a MENA university - Nader Elsayed (18060043) (2024)
Drawing on experiential learning theory (ELT), this study (1) explores students' perceived benefits of experiencing different learning styles through an audit simulation (AS) assignment and (2) analyses its role in enhancing students' performance at a Middle East and North Africa (MENA) university. The study compares students' performance across two different periods, 2019 and 2022, with 46 and 48 participants, respectively, independently completing a questionnaire of six open‐ended questions paired with follow‐up feedback, the instructor's observations and the analyses of students' grades. Our study findings indicate that the AS assignment enabled students to effectively experience different learning styles at different times during the AS learning process. They visualised an authentic AS experience by critically analysing and practically evaluating AS documents while showing strong preferences for initiating new experiences. It also reveals an improvement in students' grades after the AS implementation. Our study has theoretical implications relating to cognitive and constructivist learning, learning transfer and ethics awareness, as well as practical implications in audit education, skill development, teamwork, professional development, auditors' evaluation and curriculum assessment in other disciplines than auditing. Other Information Published in: International Journal of Auditing License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/ijau.12345